Astronomy (Boston, MA., 2005)
Prentice Hall Science Explorer-Astronomy. School textbook. Chapters include:Exploring Space, The Solar System, Earth, Moon and Sun, and Stars, Galaxies, and the Universe. 2009 Edition, Hardcover
Keywords: Science,Scientific recreations,science museums; Experiments,Educational aspects; Juvenile literature